PENERAPAN MANAJEMEN MUTU TERPADU DALAM MENINGKATKAN KEPUASAN SISWA DAN GURU - Ayuashari, Andi Ratu; Ahlun Ansar; Nuraisah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Improving the quality of educational services has become a major demand for schools in meeting student and teacher satisfaction as users of educational services. One relevant approach to addressing this challenge is the implementation of Integrated Quality Management or Total Quality Management (TQM). This study aims to describe the implementation of TQM and analyze its contribution to improving student and teacher satisfaction at UPT SPF SMP Negeri 40 Makassar. The research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The informants consisted of two students and two teachers selected based on their active involvement in the learning process and school quality management. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of TQM principles positively influences student and teacher satisfaction. Learning services become more effective through interactive methods and the use of technology such as smartboards, which enhance student participation and understanding. School facilities generally support the learning process, although optimization is still needed, particularly in laboratory utilization and the availability of textbooks. A relatively clean and harmonious school environment contributes to learning comfort. From the teachers’ perspective, management support, effective communication, periodic supervision, and opportunities for professional development strengthen motivation and performance. Therefore, the implementation of Total Quality Management significantly contributes to improving educational service quality and sustaining student and teacher satisfaction.